치과위생사를 위한 방사선안전관리교육 필요성에 대한 고찰 - 이새롬; Sae-rom Lee; 강주희; Ju-hee Kang (Han'guk Ch'iwisaeng Hakhoe chi, 2023)
Objectives: The purpose of this study is to recognize the need for dental hygienists to receive radiation safety management training as dentists are required to receive radiation safety officer continuing education every two years. Methods: This study reviewed the current radiation safety officer training, identified the scope of radiation work performed by dental hygienists, and discussed the need for radiation safety management training with a focus on dental hygienists. Results: Through improved awareness and continuous education on radiation safety management, we will later consider patient exposure management and dose management for dental hygienists. Conclusions: It is necessary to establish a dental radiation safety culture that strives to reduce harm to patients undergoing imaging for dental care through radiation safety management education of dental hygienists who are radiation safety manager.